Occuli Dextra Proptosis in Symptomatic Hiperthyroidism with Diffuse Goitre in 45-Year-Old-Woman: A Case Report with Literature Review - Novitasari, Diana (Syntax Corporation, 2025)
Thyroid hormones have been shown to impact the uptake and transportation of iron. By binding to a functioning TSH receptor, which is present in erythrocytes and certain extrathyroidal organs, TSH may have an effect on hematopoiesis. There are common causes for both poor thyroid status and anemia, which could account for the co-occurrence of low thyroid function and anemia. We report the case of 45 -year-old woman with major complaints of Swelling on her neck. Swelling on this patient occur with palpitations. On local examination of the neck area, there was visible mass during inspection, and on palpation there mass in the neck area. On laboratory examination, TSHs levels were 5.6 uIU/mL, FT4 levels were 128pmol/L, Hemoglobin 7.7 µg/dL. The patient underwent oral theraphy with using Salmon DNA on her diet and after 1 month control Her lab turn out very well with TSHs levels were 4,1 uIU/mL, FT4 levels were 22 pmol/L, Hemoglobin 10 µg/dL.